Heterogeneous microstructural changes of the cervix influence cervical funneling. (1st March 2022) - Moghaddam, A. Ostadi; Lin, Z.; Sivaguru, M.; Phillips, H.; McFarlin, B.L.; Toussaint, K.C.; Johnson, A.J. Wagoner
Abstract: The cervix acts as a dynamic barrier between the uterus and vagina, retaining the fetus during pregnancy and allowing birth at term. Critical to this function, the physical properties of the cervix change, or remodel, but abnormal remodeling can lead to preterm birth (PTB). Although cervical remodeling has been studied, the complex 3D cervical microstructure has not been well-characterized. In this complex, dynamic, and heterogeneous tissue microenvironment, the microstructural changes are likely also heterogeneous. Using quantitative, 3D, second-harmonic generation microscopy, we demonstrate that rat cervical remodeling during pregnancy is not uniform across the cervix; the collagen fibers orient progressively more perpendicular to the cervical canals in the inner cervical zone, but do not reorient in other regions. Furthermore, regions that are microstructurally distinct early in pregnancy become more similar as pregnancy progresses. We use a finite element simulation to show that heterogeneous regional changes influence cervical funneling, an important marker of increased risk for PTB; the internal cervical os shows ∼6.5x larger radial displacement when fibers in the inner cervical zone are parallel to the cervical canals compared to when fibers are perpendicular to the canals. Our results provide new insights into the microstructural and tissue-level cervical changes that have been correlated with PTB and motivate further clinical studies exploring the origins of cervical funneling. Statement of significance: Cervical funneling, or dilation of the internal cervical os, is highly associated with increased risk of preterm birth. This study explores the 3D microstructural changes of the rat cervix during pregnancy and illustrates how these changes influence cervical funneling, assuming similar evolution in rats and humans. Quantitative imaging showed that microstructural remodeling during pregnancy is nonuniform across cervical regions and that initially distinct regions become more similar. We report, for the first time, that remodeling of the inner cervical zone can influence the dilation of the internal cervical os and allow the cervix to stay closed despite increased intrauterine pressure. Our results suggest a possible relationship between the microstructural changes of this zone and cervical funneling, motivating further clinical investigations. Graphical abstract: Image, graphical abstract